2011
DOI: 10.1128/aac.00921-10
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Clavulanic Acid-Inhibited Extended-Spectrum β-Lactamases in Aeromonas spp. from the Seine River, Paris, France

Abstract: Environmental Aeromonas sp. isolates resistant to ceftazidime were recovered during an environmental survey performed with water samples from the Seine River, in Paris, France, in November 2009. Selected isolates were identified by sequencing of the 16S rRNA and rpoB genes. PCR and cloning experiments were used to identify broad-spectrum-␤-lactamase-encoding genes and their genetic context. Clavulanic acid-inhibited extended-spectrum-␤-lactamase (ESBL) genes were identified in 71% of the Aeromonas sp. isolates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 45 publications
(39 reference statements)
2
52
0
1
Order By: Relevance
“…isolates and was found more frequently among isolates from polluted sites. Recently, in several environmental studies, members of the same genera have been identified as ESBL producers, enforcing their relevance and importance for resistance monitoring (14,15,27). We investigated the presence of different ESBL genes and found bla CTX-M genes to be the most prevalent, followed by bla TEM genes.…”
Section: Discussionmentioning
confidence: 99%
“…isolates and was found more frequently among isolates from polluted sites. Recently, in several environmental studies, members of the same genera have been identified as ESBL producers, enforcing their relevance and importance for resistance monitoring (14,15,27). We investigated the presence of different ESBL genes and found bla CTX-M genes to be the most prevalent, followed by bla TEM genes.…”
Section: Discussionmentioning
confidence: 99%
“…The number of studies investigating rivers as potential reservoirs of ESBL producers is still very limited (19,20,21,22,23), and data from only one river (Seine River, Paris, France) in central Europe are available (22). Rivers and lakes are considered especially relevant as putative reservoirs of multiresistant bacteria, since they collect surface waters containing materials from different origins, e.g., wastewater plants, water of urban or industrial effluents, agricultural activities, or rain.…”
Section: Discussionmentioning
confidence: 99%
“…Phage-related elements are associated with bla CTX-M genes (Oliver et al, 2005) and Re1-like sequences have been identified in association with bla VEB-like and bla PER genes (Girlich et al, 2011).…”
Section: Insertion Sequences and Transposonsmentioning
confidence: 99%
“…ESBLs (CTX-M, PER) and/or AmpC (CMY-2) enzymes have been detected among potential human and fish pathogens in these settings, such as Salmonella, Aeromonas, Vibrio, and Edwarsiella ictaluri (Doublet et al, 2009;Girlich et al, 2010Girlich et al, , 2011McIntosh et al, 2008;Picao et al, 2008;Welch et al, 2009). …”
Section: 2mentioning
confidence: 99%